Relationship between arterial stiffness parameters and the extent and severity of coronary artery disease - Kızılırmak Yılmaz, Filiz; Babur Güler, Gamze; Kaya, Özgür; Güler, Ekrem; Demir, Gültekin Günhan; Güneş, Hacı Murat; Olgun, Fatih Erkam; Barutçu, İrfan; Boztosun, Bilal (Elsevier Science Bv., 2017)
Background: The association between arterial stiffness (AS) and coronary artery disease (CAD) has been previously demonstrated. In the present study, we aim to investigate the relationship between various AS parameters and the extent and severity of CAD. Methods: The study population consisted of 411 patients with CAD documented by coronary angiography. We measured various AS parameters including augmentation index (AIx), augmentation pressure (AP), pulse wave velocity (PWV), central systolic pressure (cSys), central diastolic pressure (cDia) and central pulse pressure (cPP) with pulse wave analysis. Angiographic images were used to calculate Gensini score and Syntax score. AS parameters were compared using Gensini score and Syntax score. Results: Syntax score is correlated with age, cSys, cPP, PWV, AP, brachial pulse pressure (bPP), hemoglobin, urea, diabetes mellitus, left main coronary artery disease (p < 0.10 for each). However, Gensini score is correlated only with age, diabetes mellitus, left main coronary artery disease and bPP (p < 0.10 for each). Multivariate analysis revealed age, diabetes mellitus, left main coronary artery disease and bPP as significant predictors of Syntax score; however, for Gensini score, age, diabetes mellitus, gender, left main coronary artery disease, and bPP are determined as predictors. Conclusion: AS parameters are not associated with Syntax score or Gensini score. Apart from traditional risk factors, bPP appears to be the only significant predictor for Syntax score and Gensini score.
WOS: 000410030800006
Keywords: Arterial Stiffness; Gensini Score; Syntax Score; Central Aortic Pressure